From Manila to the world 10 stories, 10 cities, one accidental globe-trotter - Mangahas, Paolo (University of Santo Tomas Publishing House, 2022)
From Manila, to the world: 10 stories, 10 cities, one accidental globe-trotter is a compilation of stories from 10 different locations that are as much tales of self-discovery as they are adventures in new places. While it is a journey into rich cultures and landscapes, this book is also essentially a journey within, presented in Mangahas’ sometimes wry, occasionally hilarious, yet always authentic voice. --Back cover.